Application of Solvent Influenced Fluorescence-quenching and Enhancement to Develop a Highly Sensitive HPLC Methodology for Analysis of Resveratrol-PEG Conjugates - Basavaraj, S; Benson, Heather; Brown, David; Chen, Yan (Bentham Science Publishers Ltd., 2013)
Quantification of pegylated drugs in biological matrices is often complex and challenging. This paper describes a sensitive HPLC method with fluorescence detection for the analysis of pegylated resveratrol, resveratrol and its metabolites. Solvent mediated fluorescence enhancement and quenching effects were explored to develop a highly sensitive HPLC method for analysis of resveratrol-PEG conjugates. The effect of solvent composition on fluorescence intensity of resveratrol-PEG conjugate was evaluated by varying the concentration of methanol in the solvent mixture. The fluorescence intensity of resveratrol-PEG was found to be dependent on the methanol concentration and was at maximum at 100% methanol. The HPLC assay method developed, with a linear gradient, allowed the maximum detection of the resveratrol- PEG conjugate with methanol at 95% of the mobile phase without affecting sepertion of resveratrol and its metabolites. The LOQ for resveratrol-PEG was 300 ng/mL (equivalent to 30 ng/mL resveratrol), nearly ten times more sensitive than HPLC with UV detection (3 µg/mL). The peaks detected for resveratrol-PEG, resveratrol and its metabolites in HPLC were identified qualitatively by LC/MS and LC-MS/MS (metabolites) and found to correlate with their respective molecular masses. The results of this study demonstrate that the developed HPLC assay method can accurately and selectively quantify resveratrol-PEG conjugates in the presence of resveratrol metabolites without affecting the sensitivity of resveratrol analysis. The application of solvent mediated fluorescence enhancement in HPLC potentially permits the analysis of, not only resveratrol-PEG conjugates, but also other resveratrol-polymer conjugates in samples obtained from in vitro or in vivo biological studies.